Determination of the structural ensemble of the molten globule state of a protein by computer simulations. Issue 8 (24th April 2019) - Shimizu, Masahiro; Kajikawa, Yukihito; Kuwajima, Kunihiro; Dobson, Christopher M.; Okamoto, Yuko
Abstract: We have used computer simulations to investigate the structural nature of the molten globule (MG) state of canine milk lysozyme. To sample the conformational space efficiently, we performed replica‐exchange umbrella sampling simulations with the radius of gyration as a reaction coordinate. We applied the Weighted Histogram Analysis Method to the trajectory of the simulations to obtain the potential of mean force, from which we identified representative structures corresponding to local minima in the free energy surface. The representative structures obtained in this way are in accord with the characteristics of the MG state reported previously by experimental studies. We conjecture that the MG state comprises a series of partially structured states undergoing relatively fast conformational interchange.